Rendering Invisible Punishments Visible: Using Institutional Ethnography in Feminist Criminology. (October 2014) - Welsh, Megan; Rajah, Valli
As the pendulum swings away from mass incarceration, feminist criminologists must be alert to the ways in which forms of invisible punishment continue to oppress and marginalize crime-processed women. Institutional ethnography is a mode of inquiry that examines work processes and how they are coordinated, often through texts and discourses. Through illustrative examples from a sample of formerly incarcerated women in post-realignment California, we demonstrate institutional ethnography's importance as a feminist research tool that places the reentry work of crime-processed women in conversation with the invisible punishments imposed on them after and in lieu of incarceration.